IMF Staff papers : Volume 32 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1985)
The monetary approach, however, is based on a balance-sheet identity that does not itself yield testable hypotheses. Predictions capable of being disproved can be derived only from a structural model used in conjunction with this approach. This paper analyzes the behavior of a small open economy in an alternative Keynesian framework that is characterized by short-run nominal wage rigidity and in which prices in a nontraded-goods sector are set by way of a mark-up equation. This Keynesian variant can generate short-run deviations of output from capacity as well as fluctuations in real exchange rates and real interest rate differentials. Nevertheless, it remains firmly embedded in the monetary approach. If this model represents an accurate description of an economy's short-run behavior, then framing stabilization program under 'global monetarist' assumptions may well confront policymakers with undesirable consequences for the domestic economy while leaving them short of their balance of payments target.